Acute Kidney Injury in Decompensated Cirrhosis Is Associated With Both Hypo‐coagulable and Hyper‐coagulable Features. Issue 4 (14th October 2020) - Zanetto, Alberto; Rinder, Henry M.; Campello, Elena; Saggiorato, Graziella; Deng, Yanhong; Ciarleglio, Maria; Wilson, Francis P.; Senzolo, Marco; Gavasso, Sabrina; Bulato, Cristiana; Simioni, Paolo; Garcia‐Tsao, Guadalupe
Abstract : Background and Aims: Recent evidence suggests that acute kidney injury (AKI) is the main predictor of postparacentesis bleeding in patients with cirrhosis. To assess the factors responsible for bleeding tendency in AKI, we performed a prospective study comparing all three aspects of hemostasis (platelets, coagulation, and fibrinolysis) in patients with decompensated cirrhosis with and without AKI. Approach and Results: Primary hemostasis assessment included platelet aggregation and secretion (platelet function markers) and von Willebrand factor. Secondary hemostasis assessment included pro‐coagulant (factor VIII and factor XIII) and anti‐coagulant (protein C, protein S, and antithrombin) factors and thrombin generation. Tertiary hemostasis assessment included fibrinolytic factors and plasmin‐antiplasmin complex. Eighty patients with decompensated cirrhosis were recruited (40 each with and without AKI). Severity of cirrhosis and platelet count were comparable between groups. Median serum creatinine was 1.8 mg/dL and 0.8 mg/dL in patients with and without AKI, respectively. At baseline, patients with cirrhosis and AKI had lower platelet aggregation and secretion, indicative of impaired platelet function (increased bleeding tendency), without differences in von Willebrand factor. Regarding coagulation factors, factor VIII was higher, whereas protein C, protein S, and antithrombin were all lower, which, together with increased thrombin generation, indicate hypercoagulability. In contrast, factor XIII was lower in AKI (increased bleeding tendency). Finally, while both hypofibrinolytic and hyperfibrinolytic changes were present in AKI, a higher plasmin‐antiplasmin complex indicated a hyperfibrinolytic state. After AKI resolution (n = 23 of 40), platelet function and coagulation improved to levels observed in patients with cirrhosis patients without AKI; however, fibrinolysis remained hyperactivated. Conclusions: In patients with decompensated cirrhosis, AKI is associated with both hypocoagulable and hypercoagulable features that can potentially increase the risk of both bleeding and thrombosis.